Circular Economy Approach in the Utilization of Cl? Purification Process Waste into Aluminum sulfate - Brayan Multirizky Pradana; Erwan Adi Saputro; Silvana Dwi Nurherdiana; Srie Muljanie (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study aims to analyze the potential utilization of sulfuric acid waste (H?SO?) from the Cl? purification process into alum (Al?(SO?)?) and to evaluate its implementation in supporting the concept of circular economy and sustainable environmental management. The research was conducted through an alum synthesis process using a reaction between H?SO? waste and aluminum hydroxide (Al(OH)?) with variations in Al(OH)? weight and stirring speed. Product characteristics were analyzed based on Al?O? content, physical properties, economic potential, and the level of system circularity using Recycling Rate and Circularity Rate indicators. The results showed that increasing the amount of Al(OH)? increased the Al?O? content in the alum product, with the highest value of 18.21% obtained at a stirring speed of 150 rpm and the addition of 300 grams of Al(OH)?. The resulting alum products exhibited denser and more homogeneous physical characteristics at higher aluminum concentrations. Based on the mass balance analysis, 300 liters of H?SO? waste were able to produce approximately 391 kg of Al?(SO?)?. From the circular economy perspective, the Recycling Rate and Circularity Rate values obtained were 80.9% and 72.8%, respectively, indicating a high level of waste reutilization within the production system. In addition to providing environmental benefits through the reduction of hazardous waste, this process also offers potential savings in industrial operational costs. Therefore, the utilization of sulfuric acid waste into alum is considered technically, economically, and environmentally feasible as an implementation of the circular economy concept in the chemical industry. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 15: Life on Land